2013
DOI: 10.1097/01.xha.0000423419.15162.b0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of arousal and orgasmic disorders in women with female genital mutilation/cutting

Abstract: ObjectiveThe aim of this study was to compare the sexual function in women who had undergone female genital mutilation/cutting (FGM/C) with that in those who had not. SettingThe study was carried out at the Outpatient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In our study, we found that the frequency of orgasm was lower in the genitally cut women than the uncut ones. This result was supported by the study of Moamen et al [14] ; where there were statistically significant differences in arousal and orgasm scores detected between the genitally cut and uncut women, with higher scores among genitally uncut women, which were more evident above the age of 30 years. Also, this result agreed with [9,15,[18][19] who also found that the cut women were less orgasmic than uncut ones, that can be explained as women experienced two kinds of orgasm clitoral and vaginal.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In our study, we found that the frequency of orgasm was lower in the genitally cut women than the uncut ones. This result was supported by the study of Moamen et al [14] ; where there were statistically significant differences in arousal and orgasm scores detected between the genitally cut and uncut women, with higher scores among genitally uncut women, which were more evident above the age of 30 years. Also, this result agreed with [9,15,[18][19] who also found that the cut women were less orgasmic than uncut ones, that can be explained as women experienced two kinds of orgasm clitoral and vaginal.…”
Section: Discussionsupporting
confidence: 71%
“…Alkhalaileh et al [13] assessedthe extent to which prevalence of FGM/C/C have changed in Egypt since its criminalization in 2008. They reported that the prevalence of FGM/C/C among adolescent womenstatistically significantly decreased from 94% in 2008 to 88% in 2014.Among the participants of Moamen et al [14] , all the uncircumcised women as well as 40% of circumcised participants disagreed with performing circumcision on their daughters and said that it is not important, is unnecessary for a woman, and is a painful procedure.…”
Section: Discussionmentioning
confidence: 98%